Floral offer, honey and wax quality from hybrid and European bees in Nariño-Colombia - Insuasty-Santacruz, Efrén Guillermo; Jurado Gamez, Henry Armando; Lasso, Alberth Fabián Andrade (Revista de Ciencias Agrícolas, 2025)
Beekeeping is one of the most significant agricultural activities in Colombia, despite the lack of technological and industrial advancements in this field. Therefore, the floral offer and the quality of both honey and beeswax from hybrid and European bees were evaluated. The study was conducted at the University of Nariño’s apiary (Colombia). Colonies of hybrid and European bees were used to determine the floral offer and its apicultural potential, as well as the production and quality of honey and beeswax during the period from May 2022 to February 2023. Seventeen nectariferous and polliniferous plant species were found, with the Asteraceae and Fabaceae families standing out. Differences were observed in honey production, with values of 6206 g/colony for European bees and 3971 g/colony for hybrid bees. Brix degrees of 81.0 were found for hybrid bee honey and 80.0 for European bee honey, with a pH of 4.15 in hybrid bees and 4.52 in European bees. Differences were observed in beeswax production and a good physicochemical composition (moisture <2 g/100g and 2.30 g/100g in hybrid and European bees, respectively). Microbiological results showed the absence of Salmonella and Escherichia coli <10 CFU/100g in the beeswax of both types.